Straightforward Synthesis of Functionalized l-Quinovosamine Thioglycoside Derivatives and Their Direct Use in the Synthesis of the Tetrasaccharide Corresponding to the Cell Wall of Escherichia coli O98 - Dogra, Saikat; Sahaji, Samim; Misra, Anup Kumar (Synthesis, 2025)
Synthesis of functionalized l-quinovosamine thioglycoside was achieved in very good yield using simple functional group manipulation of l-rhamnose. l-quinovosamine thioglycoside derivatives have been successfully used in the total synthesis of the tetrasaccharide repeating unit of the cell wall O-antigen of Escherichia coli O98 strain. Two units of l-quinovosamine thioglycoside were stereoselectively glycosylated during the synthesis of the tetrasaccharide. In addition, direct conversion of azido groups into acetamido functionality and TEMPO-mediated (diacetoxyiodo)benzene (DAIB) oxidation of a primary hydroxyl group to a carboxylic group are noteworthy features of the synthetic strategy.
Keywords: Carbohydrates; Glycosylation; Glycoside; Oligosaccharide; Synthesis; Escherichia coli